PENGARUH STORE ATMOSPHERE DAN CUSTOMER VALUE TERHADAP KEPUASAN PELANGGAN MIXUE(Studi Pada Mahasiswa di Kota Medan) - Sauhur Destia Waruwu; Ainun Mardhiyah (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
The phenomenon of many beverage businesses in Indonesia makes beverage entrepreneurs have to get the attention of the public because they have to compete with many similar companies. Store atmosphere is one example that can provide a different experience to consumers. Store atmosphere is something that customers pay attention to when going to the store. In increasing competitiveness, customer value is also needed. Customer value is defined as the value or benefit felt by customers from a product or service compared to the sacrifices made to get it. This study aims to analyze the influence of store atmosphere and customer value on Mixue customer satisfaction for students in Medan City. The effect between store atmosphere and customer value will be analyzed partially and simultaneously on customer satisfaction.The research method used is quantitative research with an associative approach. Sampling was done through purposive sampling technique and used 100 respondents as samples. Primary data in this study were obtained by distributing questionnaires, while secondary data were obtained through literature studies. The data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that the store atmosphere and customer value variables had a significant effect both partially and simultaneously on customer satisfaction. The coefficient of determination test shows that there is a fairly close relationship between store atmosphere and customer value on customer satisfaction with an R value of 0.714. Through the adjusted R square value, it is also known that store atmosphere and customer value variables contribute 71.4% to the purchase satisfaction variable while the remaining 28.6% is influenced by other variables not discussed in this study